Processes of large-scale land acquisition by investors: Case studies from Sub-Saharan Africa - German, L.; Schoneveld, George C.; Mwangi, E. (Land Deals Politics Initiative, 2011)
Rapid growth of emerging economies, emerging interest in biofuels as an alternative to fossil fuels and recent volatility in commodity prices have led to a marked increase in the pace and scale of foreign direct investment in land-based enterprises in the global South. Recent publications on the social and environmental effects of these large-scale land transfers and growing concern from civil society have placed the subject of “global land grabs” firmly on the map of global land use change and public discourse. Yet what are the processes involved in these large-scale land transfers? Based on a review of policy documents, interviews with government officials from diverse sectors and discussions with customary leaders and affected communities, this paper provides a comparative analysis of legal and institutional frameworks and actual practices associated with large-scale land acquisitions in Ghana, Mozambique, Tanzania and Zambia. Results suggest that in many cases it is not a global “land grab” driven by the private sector, but a supply-driven process in which governments are playing an active role – often bolstered by an unwavering faith in the role of foreign investment in national economic development. They also suggest that customary rights are seldom adequately protected in the context of land negotiations despite widespread legal recognition of these rights. The fact that results are strikingly similar despite a wide variety of legal and institutional frameworks for protecting customary rights and regulating large-scale land acquisition raises an analytical challenge which is discussed in the final section as a means of distilling implications for governance.